Epidemiological Features of Sexually Transmitted Infections in the Republic of Tatarstan - Zh. G. Eremeeva; R. Z. Ibragimova; S. T. Agliullina (Эпидемиология и вакцинопрофилактика, 2020)
Relevance. Sexually transmitted infections (STIs) remain an urgent problem in modern society due to the high incidence of morbidity, the development of complications, including cancer, affecting the reproductive health of the population. The purpose of the study is to assess the incidence of sexually transmitted infections in the Republic of Tatarstan, including the incidence of certain nosoforms (syphilis, gonorrhea, trichomoniasis, chlamydial infection anogenital warts and urogenital herpes) in the period 2013–2017. Material and methods. A descriptive epidemiological study was conducted-a retrospective analysis of the incidence of STIs in the Republic of Tatarstan. We analyzed the long-term dynamics of the overall incidence of STIs, as well as for the nosoforms of STIs for the period from 2013 to 2017. The data was processed using Microsoft Excel 2010 and OpenEpi online calculators. Results. There is a statistically significant downward trend in the overall incidence of STIs in Russia, RT, and Kazan in 2013–2017 (p < 0.05). The incidence of STIs is higher in Kazan and the Republic of Tatarstan in comparison with the incidence of the population of the Russian Federation. A statistically significant decrease in the incidence of syphilis, gonorrhea, trichomoniasis, chlamydia, and anogenital warts was detected in 2013–2017 (p < 0.05). Among the nosologies of STIs, anogenital warts have the highest incidence rates (84.8 cases per 100 ths) and occupy the 1st place in the structure of STIs in the Republic of Tatarstan (53.3% in 2017). Conclusion. The long-term dynamics of morbidity is characterized by a statistically significant downward trend in the overall incidence of STIs in the Republic of Tatarstan in 2013–2017. Anogenital warts dominate the structure of STI in the Republic of Tatarstan.